การคำนวณปริมาณยาคาร์โบพลาตินโดยใช้สูตรการประมาณค่าอัตราการกรองของไตของประชากรไทยเปรียบเทียบกับการใช้สูตรของค็อกครอฟท์-กอล์ท - ก่อเกียรติ์ กังวาลทัศน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
Background: In current practice, carboplatin dose is calculated by Calvert formula. Although, originally measured glomerular filtration rate (GFR) was used in the formula, creatinine clearance (CrCl) estimation by Cockcroft-Gault (CG) formula is widely accepted. The estimated GFR (eGFR) by Thai eGFR equation based on serum creatinine level has been established and endorsed to apply in clinical practice. However, there was a discrepancy between CG formula and Thai eGFR reported in the practice. Thus, we conducted a cross sectional study to compare accuracy of calculation carboplatin dosage between CG formula and Thai eGFR by used 24 hours urine CrCl to be a reference value. Patients and methods: Patients receiving carboplatin based regimens at King Chulalongkorn Memorial Hospital were enrolled. Before the chemotherapy session, patients were collected blood and urine 24 hours for measure plasma creatinine level and 24 hours urine CrCl, respectively. Based on the carboplatin dosage which calculated from 24 hours urine CrCl, we compared the accuracy of carboplatin dose calculation by CG formula and Thai eGFR equation. Results: Of total 108 enrolled patients, 61.1% were male and the mean age was 61.2 years. The mean BMI was 21.9 (13.4-36) kg/m2 and mean plasma creatinine levels was 0.80 (0.29-2.56) mg/dl. Lung cancer was the most common diagnosis (42.6%) and majority was received carboplatin with paclitaxel regimen (23.1%). The mean carboplatin dosage which calculated by urine CrCl, CG formula and Thai eGFR were 537.9 (±210.3), 532.3 (±167.4) and 580.9 (±162.1) mg, respectively. The mean percentage error (MPE) of carboplatin dosage which calculated by CG and Thai eGFR were 3.7 (±23.3) and 14.9 (±28.6) %, respectively, p<0.001. Conclusions: The Calvert formula using CG formula is more accurate than using Thai eGFR in Thai cancer patients.